The Intimate Responsibility of Surrogate Decision-Making - Lindemann, Hilde (The Hastings Center report, 2018)
Daniel Brudney's clear-headed analysis, in this issue of the Hastings Center Report, of the difference between a patient's and a surrogate's right to make medical treatment decisions contributes to a longstanding conversation in bioethics. Brudney offers an epistemological and a moral argument for the patient's and the surrogate's right to decide. The epistemological argument is the same for both parties: the (competent) patient has a right to decide because she is presumed to know her own interests better than anyone else, and the surrogate is entitled to make decisions because she knows the patient better than anyone else. However, argues Brudney, the moral arguments are not parallel. The patient's moral right to decide for herself is an exercise of autonomy, but the only ground for the responsibility held by the surrogate, says Brudney, is that she knows the patient better than the health care professionals do. If in fact that's not the case, then she forfeits her right to be the patient's surrogate. For all the clarity and force of his argument, I think Brudney may be barking up the wrong tree. In cases of proxy decision-making, it's intimacy, not knowledge, that does the heavy moral lifting.